Strategic asset seeking and innovation performance: The role of innovation capabilities and host country institutions - Lili Mi; Xiao-Guang Yue; Xue-Feng Shao; Yuanfei Kang; Yulong Liu (Journal of Risk and Financial Management, 2020)
Peering through the lenses of the strategic intent perspective and strategic fit paradigm, in this study, we seek to examine the contingent conditions under which emerging market multinational enterprises (EMNEs) with strategic asset seeking (SAS) intent can achieve improved innovation performance. We developed a contingency model of how the relationship between SAS intent and innovation performance is contingent on the moderating effects of firms' innovation capability and institutional quality in the host country, as well as on the synergistic interaction of independent moderating effects from these two factors. We combined survey data from 320 Chinese MNEs with archival data to test our hypotheses. Our results show that SAS intent can lead to positive innovation performance when (a) the investing firm has developed high levels of innovation capability, and (b) synergistic interactions exist between institutional quality and firms' innovation capability regarding their moderating effect on the SAS intent-innovation performance link.
Keywords: 330; emerging market multinational enterprises; foreign direct investment; innovation performance; strategic asset seeking intent; strategic fit